Design Manufacture and Performance Test of a Reciprocating Refrigeration Compressor - Deniz Uzunsoy; Hüseyin Lekesiz; Yusuf Ali Kara; Mustafa Gürkan Aydeniz (Hittite Journal of Science and Engineering, 2018)
The first generation of refrigeration compressors is reciprocating type compressors, the second generation is scroll type, and the third generation is screw type compressors that are available on the market. Although the need of semi-hermetic refrigeration compressor in Turkey market is 15000 per year, there is no any domestic manufacturer of semi-hermetic refrigeration compressor, and consequently Turkey imports all of the refrigeration compressors from abroad market. In this study, the performance and the manufacturing processes of the semi-hermetic refrigeration compressor that is designed and manufactured with a hundred percent of domestic opportunities are investigated. The performance tests of the compressor are done, the catalogue of the compressor is prepared and it is 12 % more efficient in comparison with equivalent European one.